Thermal-hydraulic performance of mist/compressed humid air two-phase flow in an airfoil channel recuperator. (25th January 2022) - Chen, Junlin; Guo, Jiangfeng; Li, Xunfeng; Huai, Xiulan; Cheng, Keyong
Highlights: Mist injection can improve the thermal-hydraulic performance of the recuperator. Mist injection can break through the limitation of moisture content of humid air. Pressure has little effect on the thermal-hydraulic performance of mist/air flow. Thermal-hydraulic correlations with the mist content for humid air are proposed. Abstract: The introducing water mist into the cold channel of recuperator was adopted to improve the thermal-hydraulic performance of compressed humid air in a megawatt grade humid air turbine cycle. The influences of mist content, air pressure and droplet diameter on the thermal-hydraulic performance of the humid air were numerically simulated. The results showed that when the quantity of mist increased from 0 to 16%, the pressure drop decreases by 24.35% while the Colburn factor increases by 8%. The method can effectively mediate the contradiction between heat transfer and resistance. However, the variation of air pressure had little effect on the thermal-hydraulic performance. Besides, the best heat transfer performance can be realized when the inlet droplet diameters are between 5 and 10 μm. A new heat transfer enhancement factor of mist content was proposed, and the correlations of the Nusselt number and friction factor were obtained. When enhancement factor increases from 0 to 0.16, the Nusselt number increases by 141.5%, and the friction factor decreases by 86.4%. The method of injecting mist can improve the thermal-hydraulic performance and reduce the volume of recuperator, which is further beneficial to reduce the cost and promote the thermal efficiency in the practical application of humid air turbine cycle. It has high application value in the future commercial application of humid air turbine cycle. The results and correlations can provide model and guidance for the design and application of recuperator and humid air turbine cycle.